Działalność KNSA PŁ „IX Piętro” w roku akademickim 2018/2019 - Striker, Jarosław; Włodarczyk, Daria (Lodz University of Technology. Faculty of Civil Engineering, Architecture and Environmental Engineering, 2019)
Artykuł ma formę sprawozdawczą i ma na celu przedstawić działalność Koła Naukowego Studentów Architektury Politechniki Łódzkiej „IX Piętro” w roku akademickim 2018/2019. Na działalność koła w minionym roku składały się nie tylko uczestnictwa w konferencjach, ale również ich organizacja. Poza tym osoby zrzeszone w naszym kole aktywnie pracowały nad organizacją warsztatów architektonicznych i wypraw naukowo-badawczych, nad wydaniem publikacji pokonferencyjnej oraz publikacji po wyprawie naukowej studentów architektury PŁ w Karpaty Wschodnie. Ponadto przedstawiciele „IX Piętra” reprezentowali Politechnikę Łódzką i Wydział Budownictwa, Architektury i Inżynierii Środo-wiska na licznych wydarzeniach.

The article has a reporting form and aims to present the activities of the "IX Piętro" (the “9th Floor”) Scientific Club of Architecture Students of the Lodz University of Technology in the 2018/2019 academic year. Last year's activities of the Club included not only participation, but also organization of conferences, architectural workshops and scientific and research expeditions, edition of a post-conference publication and publication after a scientific expedition of architecture students of the Lodz University of Technology in the Eastern Carpathians. Furthermore, „IX Piętro” represented the Lodz University of Technology and the Faculty of Civil Engineering, Architecture and Environmental Engineering at numerous events.